Edukasi Ibu Hamil Dan Konseling Tentang Tanda Bahaya Ibu Hamil Dengan Kecemasan Di Wilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu - Sulastri, Mepi; Ayudiah, Febra; Putri, Yesi (Jurnal Dehasen Mengabdi, 2024)
Puskesmas Sawah lebar is one of the health centers in Bengkulu City which is located at Jalan bukit barisan No. 2, sawah lebar, ratu agung sub-district, Bengkulu City, covering 3 villages. Based on data from the Bengkulu City Health Office in 2016 who experienced symptoms of depression and anxiety 2.3% of 8,760 pregnant women while in 2018 there was an increase in those experiencing symptoms of depression and anxiety to 2.8% of 7,524 pregnant women (Bengkulu City Health Office, 2020). So that the purpose of the purpose of this activity is as a form of anticipation of health workers to improve the health of pregnant women in order to reduce the number of complications in pregnant women. The results of education obtained from 15 pregnant women before being given education, the results of knowledge are 13% of pregnant women have sufficient knowledge and 87% have insufficient knowledge about pregnant women's anxiety about danger signs in pregnancy. After education and assistance, 85% of pregnant women's knowledge became good and 15% were sufficient. This activity was enthusiastically received by the community in the working area of the puskesmas sawah lebar city of Bengkulu and it is hoped that later the sawah lebar puskesmas can assist and continue to educate pregnant women so that complications and anxiety of pregnant women can be prevented.